Minang oral discourse in minority ethnic communities in developing Lake Toba tourism area, Indonesia: A sociopragmatic perspective - Yuhdi, Achmad; Transliova, Lili; Barus, Frinawaty Lestarina; Wasilah, Atika; Harahap, Safinatul Hasanah (Research Journal in Advanced Humanities, 2025)
This study explores the strategies of minority communities in the Lake Toba tourist area in maintaining harmony through a sociopragmatic study. It recommends developing tourism potential by strengthening local branding and effective communication patterns between minority and majority ethnic groups. This study uses sociopragmatic theory to analyze data collected through observation, in-depth interviews, documentation, literature, and field notes in 7 district locations around the Lake Toba area. This study explains the blending and politeness of speech acts in the Minang community in the Lake Toba area. The indigenous community and newcomers from different cultures agreed to merge through an indirect agreement. The Minangkabau community practices assertive communication behavior and follows certain sayings and proverbs. Various speech acts of the Minang community can be categorized as assertive, directive, commissive, and expressive. The study also noted that the most dominant speech act is the directive act.